CROI 2018: Advances in Antiretroviral Therapy - Tieu, Hong-Van (Top Antivir Med, 2018)
The 2018 Conference on Retroviruses and Opportunistic Infections (CROI) showcased exciting data on new investigational agents including MK-8591 and tri-specific antibody targeting 3 highly conserved epitopes on HIV-1 in a single antibody. Clinical trials of initial antiretroviral therapy (ART) and switch studies involving bictegravir/emtricitabine/tenofovir alafenamide were presented. Intensification of initial ART with integrase strand transfer inhibitors did not increase the risk of immune reconstitution inflammatory syndrome. Pharmacokinetic issues were discussed, including the substantial drug-drug interactions between efavirenz-based ART and hormonal contraception delivered via a vaginal ring. Studies on pre-ART drug resistance and emergence of drug resistance after initial and second-line ART in different settings and populations were highlighted. Novel technologies to identify drug resistance included a free, cloud-based web service for HIV genotyping analysis and a promising technology for point-of-care drug resistance mutations testing. New strategies to improve the HIV care continuum included home-based testing with initiation of same-day ART and stratified care with specialized clinics to serve those disengaged in care, but the data on financial incentives were not encouraging. Several studies provided insights into the impact of early ART on decreasing the size of the HIV reservoir in HIV-infected infants. Pertinent conference findings relating to women's health issues included similar clinical outcomes between breastfeeding and formula feeding HIV-infected women, the problem of viral rebound and ART nonadherence in pregnancy and postpartum.